2023
DOI: 10.3390/foods12183458
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde Inhibits Postharvest Gray Mold on Pepper Fruits via Inhibiting Fungal Growth and Triggering Fruit Defense

Lifei Yang,
Xiaoli Liu,
Haiyan Lu
et al.

Abstract: Gray mold infected with Botrytis cinerea frequently appears on fruits and vegetables throughout the supply chain after harvest, leading to economic losses. Biological control of postharvest disease with phytochemicals is a promising approach. CA (cinnamaldehyde) is a natural phytochemical with medicinal and antimicrobial activity. This study evaluated the effect of CA in controlling B. cinerea on fresh pepper fruit. CA inhibited B. cinerea growth in vitro significantly in a dose- (0.1–0.8 mM) and time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Huang et al (2019) evaluated the antifungal mechanism of trans-cinnamaldehyde against Penicillium italicum and observed that the plasma membrane of the mold had been severely destroyed and the cell wall collapsed. The antifungal activity of cinnamaldehyde against Botrytis cinerea was closely related to reactive oxygen species (ROS) accumulation and oxidative injury in both mycelia and spores (Yang et al, 2023). Wang et al ( 2023) demonstrated that the clove extract exhibited inhibitory activities against Botryosphaeria dothidea causing damage in cell membrane integrity and biological function via downregulating the genes involved in the membrane component and transmembrane transport.…”
Section: Mycelium Characteristics and Changes In Growthmentioning
confidence: 99%
“…Huang et al (2019) evaluated the antifungal mechanism of trans-cinnamaldehyde against Penicillium italicum and observed that the plasma membrane of the mold had been severely destroyed and the cell wall collapsed. The antifungal activity of cinnamaldehyde against Botrytis cinerea was closely related to reactive oxygen species (ROS) accumulation and oxidative injury in both mycelia and spores (Yang et al, 2023). Wang et al ( 2023) demonstrated that the clove extract exhibited inhibitory activities against Botryosphaeria dothidea causing damage in cell membrane integrity and biological function via downregulating the genes involved in the membrane component and transmembrane transport.…”
Section: Mycelium Characteristics and Changes In Growthmentioning
confidence: 99%
“…It poses a significant threat to the productivity of tomato crops by infiltrating multiple plant components, including stems, leaves, and fruits, thereby compromising food safety [5]. Botrytis cinerea has a strong environmental adaptability and produces spores that can easily infect nearby plants [6].After harvest, this pathogen can persist as mycelium, with or without conidia and sclerotia, in crop wastes [7]. Unfortunately, to date, there are still no reports on resistant tomato varieties [8].…”
Section: Introductionmentioning
confidence: 99%